CO2 capture in chemically and thermally modified activated carbons - Gonçalves, Carmem Natália de Pina (2017)
In the pre-industrial era the great world powers were not preoccupied with the level of global warming since fossil fuels were not much explored. But the industrial revolution changed everything, as these energy sources started being used in the petrochemical industries as well as in metallurgical industries resulting in an increased worry concerning greenhouse gases. Among the greenhouse gases, the carbon dioxide gas is one of the most common and impactful, as we are living in a world where the industrial development continues to grow and with that, it can be said that new technologies have been developed to reduce the greenhouse gases quantity in the atmosphere and consequently decrease global warming. Adsorption is one of those technologies and several adsorbent materials have been developed as well. To reach the objective of capturing the carbon dioxide a lot of studies have been made, to find an adsorbent with good adsorption capacity and that is easily accessible in economic terms. Activated carbon as adsorbent is the perfect candidate for carbon dioxide capture by adsorption due to being economically viable and having a very significant surface area, as its superficial surface can be improved by means of chemical and thermal modifications. The 6 samples studied in this work were treated with: sulfuric acid (PACSA), nitric acid (PACNA), hydrogen peroxide (PACHP) and urea (PACNAU). And the thermal treatment used in the sample which was treated with urea occurred in a temperature range between 400-850 °C (PACNAUT). The ability of adsorbing carbon dioxide for each sample at different temperatures was measured. The best results were from the PACNAUT sample at temperatures of 40, 70 and 100 ºC at 5 bar pressure where the adsorbed amount was 4,4537, 2,9805 e 2,1690 mmol g-1 respectively. Which means, that the PACNAUT is the best sample.